THE MORAL LEADERSHIP IN BUILDING LEARNING ORGANIZATION CULTURE AT THE EXCELLENT SCHOOLS - Masrukhin, Masrukhin (QUALITY, 2014)
Abstract : Focus and aim of this this research is to find and describe:(1) the characteristics of learning organization culture at excellentschool; (2) leadership style in building learning organization culture;(3) leadership in building learning organization culture in excellentschool i.e MAN 2 Kudus, MA TBS Kudus and MA NU BANATKudus. This research uses qualitative approach with multi casesstudy plan. The data collected through three techniques: 1). indepthinterview; 2). participant observation; and 3). documentation. Thereare two stages in this research, those are: (1) individual case dataanalysis, and (2) data analysis rushed by case. The research findingthat: (1) characteristics differences between one another MadrasahAliyah (MA). MA NU BANAT Kudus has characteristic in buildinglearning organization culture as this Madrasah presents moresystematic, innovative and creative system with the betterinfrastructure support. Education quality orientation is to meet therequirement of ISO 9000. It also has transformation leadership styleusing management principles in strong way. MAN 2 Kudus has itsown characteristic in building learning organization culture as itshows systematic, innovative and creative way with a betterinfrastructure tool supports, it also uses transformation leadershipstyle. MA NU TBS Kudus seems less systematic, innovative andcreative in building learning organization culture, with infrastructuretool support less good, and charisma type with transactional leadershipstyle. (2). Transformation leadership style affects the competitivenessand the graduate quality, as support form in all study activities. (3).This research also find new model of leadership based on moral(spiritual), with various kinds of attitude, moral, and values as form ofuswah hasanah.